Evaluation of dry eye symptoms in lecturers working in medical colleges of Nepal: An online cross-sectional study following SARS-CoV-2 outbreak - Bista, Bipin; Bista, Padam Raj; Neupane, Rasik; Gupta, Sharad; Pandey, Anwit Raj; Singh, Aastha; Yadav, Reena (Nepalese Journal of Ophthalmology, 2022)
Introduction: Dry eye is one of the frequently encountered ophthalmological disorders. Following the pandemic of Coronavirus disease 2019, use of masks and electronic devices has taken an upraise globally. These factors are one of the causes for dry eye disease. This study emphasises dry eye symptoms among lecturers working in medical colleges of Nepal. Materials and methods: This was a descriptive cross sectional study conducted among 217 lecturers working in various medical colleges in Nepal. Dry eye evaluation was done using the Ocular Surface Disease Index (OSDI) questionnaire. Analysis of data was using Microsoft Excel 2016 and IBM Statistical Package for Social Sciences (SPSS) version 26.0. Results: One fourth (25.80%) of 217 participants experienced symptoms of dry eye disease. Conclusion: Increasing use of mask and laptop during this pandemic era has shown to cause mild dry eye symptoms in lecturers working in medical colleges of Nepal. Proper care and precaution needs to be practised in order to minimise dry eye symptoms and its consequences.